Predictive value of lymphocyte-associated inflammation index in post-stroke cognitive impairment: a systematic review and meta-analysis - Mao, Feng-le; He, Xia; Huang, Xia-lian; Cheng, Yue-ming; Qin, Fu-li; Wang, Yan-qiu (Frontiers in Neurology, 2025)
BackgroundThe predictive role of the lymphocyte-associated inflammation index in post-stroke cognitive impairment (PSCI) remains controversial. Therefore, we performed an updated meta-analysis to update the evidence.MethodsThis meta-analysis was conducted following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Six databases were systematically searched from their inception to May 5, 2024. Two investigators independently conducted literature screening and data extraction for the included studies. Two investigators independently assessed the quality of the included studies using the Newcastle-Ottawa Scale (NOS). Combined effect sizes were calculated using weighted mean difference (WMD) or standardized mean difference (SMD) with 95% confidence intervals (CIs). Heterogeneity was tested using the chi-square (χ2) test (Cochran’s Q) and index of inconsistency (I2), Publication bias was assessed using funnel plots and Egger’s regression test.ResultsThis systematic review included a total of 16 studies, encompassing 3,406 patients. Meta-analysis revealed that neutrophil-to-lymphocyte ratio (NLR) levels were significantly higher in the PSCI group compared to the non-PSCI group (WMD: 1.12; 95% CI: 0.85, 1.40; p < 0.00001). Similarly, the platelet-to-lymphocyte ratio (PLR) levels were significantly higher in the PSCI group compared to the non-PSCI group (WMD: 16.80; 95% CI: 4.30, 29.29; p = 0.008). However, there was no statistically significant difference between the two groups concerning hemoglobin, albumin, lymphocyte, and platelet (HALP) scores (WMD: -12.78; 95% CI: −25.95, 0.38; p = 0.06) and lymphocyte count (WMD: -0.13; 95% CI: −0.34, 0.07; p = 0.20).ConclusionIncreased levels of PLR and NLR are strongly associated with the PSCI, which may serve as an effective tool for predicting PSCI. However, there is insufficient evidence to support a direct relationship between HALP scores, lymphocyte count, and PSCI.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/, identifier CRD42023462232.